Tugas Kepala Sekolah Sebagai Manajer, Administrator dan Supervisor di SMP Islam Yayasan Pembangunan Umat Islam (YPUI) Banda Aceh - Rifa Huwaidah; Musfiana Musfiana; Ismail Ali (Universitas Syiah Kuala, 2023)
This study aims to find out how the implementation of the principals duties as manajer, administrator and supervisorat the Islamic Middle School (YPUI) Banda Aceh. This study use qualitative methods and descriptive research types. The location of this research at Jalan Syiah Kuala, Kuta Alam District, Banda Aceh. Data collection techniques in the form of library research, observation and interviews. The subject of this study was the principal of the school, but in order to obtain more accurate information, discussions were held with other informants such as the vice principal, deputy teaching assistant, teacher and head administration. The object research is the implementation of the principal duties as a manager, administrator and supervisor. The result of thr study are (1) The implementation of the principal duties as a manager has beeb carried out property, the principal has been able to make plansregarding school programs, and is ablel to control existing organization in the school appropriately. (2) The principal in carrying out this duties as an administrator has carried out this duties properly. The method used by the school principal so that administrative activities run smoothly is to invole teachers and employees to participate in these activities. (3) The implementation of the principal duties as a supervisor has been carried out as it should, as can be seen from the class visits conducted by the scholl principal, the supervision schedule carried out by the school principal, namely twice a years, the even semester is sheld in march and the odd semester is held in September.